As metaimagens na televisão contemporânea: Rede Globo, MTV e suas vinhetas - Felipe de Castro Muanis (2010)
The specific aim of this thesis is to confirm that television meta images continue to maintain their power of interruption, being capable of separating or connecting the television flow. On television, meta images can primarily be found during program breaks, in commercials and in institutional vignettes. It is in the meta images presented during the program breaks that we can find a great variety of images, precisely because they are not necessarily ubordinated to a narrative text, disengaging image from dependence on the word. Therefore, meta images are not mere ornaments or peripheral images in the flow, but central images that can much contribute to a television theory and an image theory. In this study, the proposed investigation is an alternative to the analysis of the emission content, or still, direct transmission. For this purpose, we analyze television meta images, their differences and how they relate with the flow and the emission. The theoretical foundation in this thesis is supported by texts by John Fiske, John Thornton Caldwell, Umberto Eco, Thomas Mitchell, Francesco Cassetti, Roger Odin and Oliver Fahle, among other authors. For the purpose of this study, it is important to rethink the concepts of paleo and neotelevision proposed by Eco. Besides constituting periods of television history, they also constitute ways the viewer relates with television. On current television, there are old format programs from classic television, living together with new formats from a modern television. Neo-television was not a breakdown, but a changing process that absorbed some features of paleo-television. When there is specific viewer attention to a certain program that motivates him to be in front of the TV, there is a rescuing of the paleo-television attitude, in which the attention is primarily focused on the program and not on the flow. In such situations, the meta images would be valued as interruption for the viewer. On the other hand, when there is a flow, and the emission reading is transversal, with zapping every now and then, the viewer is said to assume a neo-television attitude, in which the contact with the flow is prioritized over the search for the emission content. Thus, the meta images would be indistinctive from other images in the flow and they would not have, in these cases, the power of interruption. Based on the view that the way of watching television is not always transversal and in flow, we confirm that the meta images, depending on the viewers attitude in relation to television, continue keeping its interruption value. However, commercials and institutional vignettes have different values in such a space, as observed in the analysis and decoupage throughout the thesis. The interest falls onto the institutional vignettes due to the range of possibilities they offer. Those possibilities can range from a closed narrative as those found in certain MTV vignettes, presenting a post-modern poetics that aggregates all the variables, to a non-narrative, like most of the institutional vignettes on Globo Television Network. The vignettes indicate the transition and transformation from paleo-television into neo-television, even though it is not possible to perceive the exact moment of this change. Finally, a broader objective of this study is to insert the vignettes and the transformation of the television image, especially meta images, into the course of image transformation itself: television, as an important contemporary audiovisual means of communication can not be neglected in discussions that contemplate studies on image theories